Adsorption Dynamics: Comparison of Adsorption Potentials of Fibrous Keratinous Materials, viz., Human Black and White Hairs - Balasubramanian, N.; Edison Raja, R.; Lalitha, K.; Prebha, S. (Asian Journal of Chemistry, 2010)
Industries, such as tanneries, textile mills and chromium platingindustries discharge effluents containing chromium and theygenerate serious disorders and diseases. Several methods ofremoval, such as precipitation, reverse osmosis and ion-exchangewere known, but they involve high capital investments. Hence,adsorption method was chosen using human black and white hairsas adsorbents by the authors. Batch-type experiments were conducted.Contact time for attaining equilibrium and pH suitable forstudy were found to be 4 h and 1.5 respectively. The equilibriumdata are analysed in the light of Langmuir and Freundlich isothermmodels and a comparative study is made with a view to exploringthe adsorption potentials of these two keratinous adsorbents.